(untitled) (Revista Apotheke, 2023)
This article examines the intersection between gender and education in the context of childreen through de use of disruptive images as devices for discussion and reflexivity. In this context, the aim was to problematize the power of images in the production Learning Circumstances (DELIGNY, 2018) about oneself and other with regard to conceptions of gender and sexualities in childhood. To do so, it started with images that challenged gender stereotypes amalgamated in the collective imagination in order to promote a more inclusive and diverse vision in the construction of identities at school. The study starts from an experience developed in a kindergarten with childreen between four and five years. As a methodology, we used the Narrative Perspective crossed by authors such as Belidson Dias and Guacira Lopes Louro to propose a Queer Pedagogy; Fernando Hernández with regard to the Educational perspective of Visual Culture, among others. This alliance between Visual Culture Studies and the Queer pesrpective made it possible to gather experimental paths based on interpretation where images act as a pedagogical devices by encouraging the sharing of oral narratives about what they saw about themselfs when establishing relationships with their sociocultural repertoires. The results obtained indicate the urgency, as well as the relevance of theme based on approaches that leverage their knowledge, confronting hegemonic discourses, binary and stereotyped concepts in search of plural, inclusive and anti-discriminatory approaches.